Dynamic, In Situ Generated Interfaces Between Carbon‐Bonded Alumina Filters and Steel During Spark Plasma Sintering/Field‐Assisted Sintering1. Issue 12 (31st October 2013) - Salomon, Anton; Emmel, Marcus; Dudczig, Steffen; Rafaja, David; Aneziris, Christos G.; Aneziris, Christos G.
<x xml:space="preserve">Abstract</x> The aim of this study was to analyze possible reactions taking place during filtration of steel melts. The heterogeneous reactions and interface creation during short‐time contact of liquid steel and newly developed carbon bonded alumina ceramic filter (Al2O3‐C) were examined. The samples were produced using spark plasma sintering (SPS) to assure the absence of liquid convection. The production of the samples included very high heating rates of up to 1000 K min−1, short holding times just above liquidus temperature and a rapid cooling. The focus of the research was put on the inorganic inclusions (endogenous as well as exogenous), agglomerates, and phase formation. Exogenous inclusions (Al2O3) were added to the steel grade 42CrMo4 by a ball milling process. The results indicate the formation of MnS inclusions due to the high sulfur content in the used steel. The formation took place at the interfaces between steel and ceramic and at the grain boundaries within the steel. Penetration of the porous ceramic body by the steel was identified. Exogenous Al2O3 inclusions were found to agglomerate, adhere at the steel/Al2O3‐C interfaces and tended to float on top of the melt.